2020
DOI: 10.1038/s41598-020-69343-x
|View full text |Cite
|
Sign up to set email alerts
|

River flow prediction in data scarce regions: soil moisture integrated satellite rainfall products outperform rain gauge observations in West Africa

Abstract: Satellite precipitation products have been largely improved in the recent years particularly with the launch of the global precipitation measurement (GPM) core satellite. Moreover, the development of techniques for exploiting the information provided by satellite soil moisture to complement/enhance precipitation products have improved the accuracy of accumulated rainfall estimates over land. Such satellite enhanced precipitation products, available with a short latency (< 1 day), represent an important and new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 54 publications
0
37
0
1
Order By: Relevance
“…However, this was rather beyond the scope of this study and should probably be conducted in areas where more ground-truth data are available than in the large sub-basins of the Zambezi River basin. Further development of these earth observation data, however, could represent an important contribution to understanding processes in data scarce areas, as demonstrated recently for the correction of precipitation reanalyses data (Brocca et al 2019), or for the validation of river flow observation data (Brocca et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, this was rather beyond the scope of this study and should probably be conducted in areas where more ground-truth data are available than in the large sub-basins of the Zambezi River basin. Further development of these earth observation data, however, could represent an important contribution to understanding processes in data scarce areas, as demonstrated recently for the correction of precipitation reanalyses data (Brocca et al 2019), or for the validation of river flow observation data (Brocca et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, this was beyond the scope of this study and should be conducted in areas where more ground-truth data are available than in the large sub-basins of the Zambezi River basin. Further investigations of this nature could contribute to understanding processes in data scarce areas, as demonstrated recently for the correction of precipitation reanalyses data (Brocca et al, 2019), or for the validation of river flow observation data (Brocca et al, 2020).…”
Section: Data Related To Evaporative Lossesmentioning
confidence: 93%
“…In ungauged basins, studies have shown that satellite rainfall products can be used as an alternative source of meteorological data important for river basin management studies (Blöschl et al 2013;Maggioni & Massari, 2018;Belete et al 2020;Brocca et al 2020). In limited gauged basins, other studies have noted the need to corroborate the existing measurements with products derived from satellite based measurements, considering their extensive and dependable global coverage (Sooroshian et al 2000;Jiang et al 2018;Lakew et al 2020).…”
Section: Introductionmentioning
confidence: 99%